Identitas nasional : menjaga identitas nasional di tengah arus globalisasi dan perkembangan digital - kamaliya, zuhri addina (Maliki Interdisciplinary Journal, 2026)
Globalization and digital development have brought profound changes to Indonesian society, particularly among the younger generation. On one hand, technological advancement offers significant benefits in terms of easier access to information, education, and communication. On the other hand, the rapid influx of foreign cultures poses a serious threat to Indonesia’s national identity, which is rooted in Pancasila values, Bhinneka Tunggal Ika, and local wisdom. This study aims to analyze the importance of preserving national identity amid the currents of globalization and digital development, as well as to identify various efforts that can be made to maintain national values in the modern era. The method used is a literature review by analyzing various relevant sources related to national identity, the impact of globalization, and the role of the younger generation. The findings indicate that national identity faces serious threats, including the erosion of local culture, the decline of nationalism, and the infiltration of foreign values that are inconsistent with the nation’s character. Efforts to preserve national identity can be made through strengthening Pancasila and character education, preserving local culture, using digital media wisely, and enhancing the active role of youth as agents of change. This study concludes that national identity must be continuously strengthened as the foundation of national unity amid the increasingly complex dynamics of change.